Organocatalytic activation of TMSCN by basic ammonium salts for efficient cyanation of aldehydes and imines - Raj, I. Victor Paul; Suryavanshi, Gurunath; Sudalai, A. (Tetrahedron Letters, 2007)
Basic ammonium salts act as highly effective catalysts for the cyanosilylation of aldehydes and in Strecker-type aminonitrile synthesis using TMSCN as cyanide source at 25 degrees C under extremely mild conditions, affording very good to excellent yields of silylated cyanohydrins and alpha-aminonitriles. (C) 2007 Published by Elsevier Ltd.
Keywords: aldehydes; aminonitriles; cyanohydrin; cyanosilylation; multicomponent reactions; TMSCN

Oxidant controlled regio- and stereodivergent azidohydroxylation of alkenes via I-2 catalysis - Prasad, P. K.; Reddi, R. N.; Sudalai, A. (Chemical Communications, 2015)
A novel, I-2 catalyzed regio-and stereodivergent vicinal azidohydroxylation of alkenes leading to 1,2-azidoalcohols in high yields (up to 92%) and excellent dr (up to 98%) has been developed. This unprecedented transformation employs NaN3 and DMF as N-and O-nucleophiles respectively. The role of DMF as the O-source in the reaction has been unequivocally proven by O-18 labelling studies.